Sustainable intuitionistic fuzzy inventory models with preservation technology investment and shortages. (10th June 2022) - Sahoo, Swagatika; Acharya, Milu; Patnaik, Srikanta
In this paper, complete backordering and partial backordering EOQ models are developed in crisp and fuzzy sense. Spending on preservation technology, the rate of deterioration of the product is kept under control. We provide a cost for carbon emissions in the EOQ model because carbon emissions are a major contributor to climate change and global warming. This paper also describes a fuzzy model by taking a generalised pentagonal intuitionistic fuzzy number for per unit holding cost and for de-fuzzification purposes, ranking generalised pentagonal intuitionistic fuzzy number is used. The main purpose of the model is to minimise the total costs. Illustration of the suggested model is conducted through numerical examples. In this problem, a convexity check of the cost function is performed and a sensitivity test is also used to study the effect of change in the values of the parameters.